Intravitreal vascular endothelial growth factor inhibitors did not increase the risk of end-stage renal disease in patients with biopsy-proven diabetic kidney disease based on matched study - Xiao, Xiang; Zhang, Junlin; Ji, Shuming; Zou, Yutong; Wu, Yucheng; Qin, Chunmei; Yang, Jia; Zhao, Yuancheng; Yang, Qin; Liu, Fang (Frontiers in Pharmacology, 2022)
Purpose: This study aimed to investigate the effects of intravitreal (IVT) VEGFi on long-term renal outcomes in patients with biopsy-proven diabetic kidney disease (DKD). Patients and methods: Patients prescribed IVT VEGFi (VEGFi group) were enrolled from a retrospective cohort with biopsy-proven DKD, and those not prescribed VEGFi (non-VEGFi group) were enrolled by 1:3 propensity score matching, adjusted for clinical and pathological baseline indicators. The primary endpoint is defined as end-stage renal disease (ESRD) and the secondary endpoint is defined as all-cause mortality. Results: Compared with patients in non-VEGFi group, patients with VEGFi had a higher proportion of diabetic retinopathy (DR) (50.9% vs. 100%, P ＜ 0.001) before matching. Standardized mean difference (SMD) of age, DR, duration of diabetes, the proportion of hypertension, eGFR, initial proteinuria, serum albumin, hemoglobin, the proportion of RAAS inhibitor and interstitial fibrosis and tubular atrophy (IFTA) were >10%. After matching, there was no significant difference in clinical pathology between the two groups. Except for the proportion of hypertension, the SMD of other indicators was <10%. Endpoints such as ESRD (Log-Rank P = 0.772) and all-cause mortality (Log-Rank P = 0.834) were not significantly different between the two groups. Conclusion: Our data suggested that IVT VEGFi did not increase the incidence of ESRD and all-cause mortality in patients with diabetes kidney disease.